Thaxterogaster laojunensis sp. nov. (Cortinariaceae) from Southwestern China - Guan, Hong-Bin; Li, Tai-Shun; Zhang, Ying; Zhao, Qi (Phytotaxa, 2025)
A new species, Thaxterogaster laojunensis, collected in the Laojun Mountains, Yunnan Province, China, is proposed based on morphological characteristic comparison and phylogenetic analyses of the internal transcribed spacer (ITS) and the large subunit rRNA (nrLSU). This species is distinguished by its viscid pileus with yellowish tones and a white margin, and a cylindrical hollow stipe without basal bulbosity. This study presents a detailed taxonomic description, illustrations, phylogenetic analysis results, and comparison with closely related taxa of the new species.